ANALISIS KESESUAIAN METODE PELAKSANAAN PENGECORAN PELAT LANTAI PADA PROYEK PEMBANGUNAN HOTEL ASTON INN LUMAJANG DENGAN SNI 2847 : 2019 - Firmansyah, Moch. Syahrul; Bima Hanggara Nashrullah; Wahyu Kartini (Kohesi: Jurnal Sains dan Teknologi, 2024)
The implementation of slab casting is a crucial stage in high-rise building construction, as it plays a role in distributing gravitational loads to other structural elements, such as beams and columns. This study aims to analyze the conformity of the slab casting method in the Hotel Aston Inn Lumajang construction project with the standards of SNI 2847:2019, specifically Article 26.5.2.1 on concrete casting and compaction, Article 26.5.3.1 on concrete curing, and Article 26.11.1.2 on formwork standards. Data was obtained through literature review and direct observation of the slab casting process for the 7th floor in Zone 3.The casting process was carried out systematically, including preparation, formwork installation, reinforcement, supervision checks, area cleaning, casting, concrete curing, and formwork removal. Each stage complied with SNI 2847:2019 standards, including area cleanliness (point a), the use of casting equipment (points d and e), continuous casting and concrete compaction (points i and j), concrete curing to maintain moisture for 28 days (point a of Article 26.5.3.1), and the use of 12mm plywood formwork that meets the standards in Article 26.11.1.2 point a on formwork standards.The analysis results indicate that the slab casting method in this project complies with the SNI 2847:2019 standards in terms of procedures, material quality, equipment usage, and field implementation.